A value chain analysis for bioenergy production from biomass and biodegradable waste: a case study in Northern Norway - Yu, Hao; Roman, Elisabeth; Solvang, Wei Deng (IntechOpen, 2018)
Source at: http://dx.doi.org/10.5772/intechopen.72346 During the past decades, the concerns of the depletion of fossil fuels and global warming caused by excess GHG emissions have become the most important driving force for the development and utilization of renewable energy resources. The successful experiences from the EU-28 have proved that bioenergy production from biomass and biodegradable waste is the most reliable and promising solution in today’s renewable energy market. This chapter presents a general model for value chain analysis of bioenergy production from biomass and biodegradable waste. In addition, a feasibility study for establishing a bioenergy plant in the northern part of Norway is given to discuss the opportunities and challenges of bioenergy production. The feedstock of the planned bioenergy plant is from local agriculture, waste management sector, fishery and livestock industry. Value chain analysis is used to balance the economic and environmental influences of the bioenergy production in the area. Furthermore, suggestions for resolving the challenges and minimizing the potential risks of bioenergy production are also discussed in this chapter